-12-2k=-2(k+4)

Simple and best practice solution for -12-2k=-2(k+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12-2k=-2(k+4) equation:


Simplifying
-12 + -2k = -2(k + 4)

Reorder the terms:
-12 + -2k = -2(4 + k)
-12 + -2k = (4 * -2 + k * -2)
-12 + -2k = (-8 + -2k)

Add '2k' to each side of the equation.
-12 + -2k + 2k = -8 + -2k + 2k

Combine like terms: -2k + 2k = 0
-12 + 0 = -8 + -2k + 2k
-12 = -8 + -2k + 2k

Combine like terms: -2k + 2k = 0
-12 = -8 + 0
-12 = -8

Solving
-12 = -8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x+135+20=x+35 | | 3(x+6)=221 | | x+40+2x-10=180 | | 1.4b+10=18 | | 34+8m=6(3m+1)-3m | | -4(2x-1)=2(3x+2)-14x | | 2a-6+5a=3-a+7 | | 3+7(-3n+6)=-4n-6 | | -6(z-2)=3 | | 17+(-3x)=14 | | 2x-10-7x=3(x-6) | | 6(7-6n)=114 | | 7(5x-4)=5+2x | | n^2+(-3)(4)=28 | | 17+(-3)=14 | | 5+X=-36 | | 2y+7=35 | | h=16t^2+52t+16 | | 4.95+11.95=64.70 | | 40+2m=-8(m+5) | | x+74+36=77 | | 5(x-3)-4(x-3)=3(x-1) | | 2x^4-10x^2+5=0 | | 10t^2-17t+6=0 | | -4w+8=-8(w+3) | | 0.23*50=1*x | | -4z=126 | | 3x-10(x+2)=1.22-7x | | 8x-1=-9+7x | | 3x+2x+8=7x-2 | | 5y=15y-90 | | x+38+90+x+68=180 |

Equations solver categories